An electrokinetic study on tunable 3D nanochannel networks constructed by spatially controlled nanoparticle assembly. Issue 2 (19th November 2014) - Choi, Eunpyo; Kwon, Kilsung; Kim, Daejoong; Park, Jungyul
Abstract : We present a thorough experimental and theoretical analysis of nanoscale electrokinetics using ion-selective nanochannel networks formed by geometrically controlled in situ self-assembled nanoparticles. Abstract : This paper proposes a novel method to form ion-selective nanochannel networks between two microfluidic channels using geometrically controlled in situ self-assembled nanoparticles. We present a thorough experimental and theoretical analysis of nanoscale electrokinetics using the proposed microplatform. The nano-interstices between these assembled nanoparticles serve as the nanopores of ion-selective membranes with equivalent pore size. Its inherent characteristics (compared with the conventional one-dimensional nanochannels) are a high ionic flux and a low fluidic resistance because these nanopore clusters have a role as collective three-dimensional nanochannel networks, which result in a highly efficient performance beneficial for various applications. Another uniqueness of our system is that the electrical characteristics (such as ion transport through the nanochannel networks and the decrease in the limiting current region) can be tuned quantitatively or even optimized by changing the geometry of the microchannel and the pH condition of the working solution or by appropriately selecting the size and materials of the assembled nanoparticles. The correlation between these tuning parameters and nanoscale electrokinetics is deeply investigated with carefully designed experiments and their mechanism is thoroughly examined by a theoretical study. We expect that the presented system and methodology can contribute to opening new application fields, such as biomolecule separation/filtering/accumulation/analysis, bioelectronics, and energy generation.